The evolution of New Zealand's health workforce policy and planning system: a study of workforce governance and health reform - Rees, Gareth H. (2019)
Introduction: While considerable attention has been given to improving health workforce planning practice, few articles focus on the relationship between health workforce governance and health reform. By outlining a sequence of health reforms, we reveal how New Zealand’s health workforce governance and practices came under pressure, leading to a rethink and the introduction of innovative approaches and initiatives. Case description: New Zealand’s health system was quite stable up to the late 1980s, after which 30 years of structural and system reform was undertaken. This had the effect of replacing the centralised medically led health workforce policy and planning system with a market-driven and short-run employer-led planning approach. The increasing pressures and inconsistencies this approach produced ultimately led to the re-centralisation of some governance functions and brought with it a new vision of how to better prepare for future health needs. While significant gain has been made implementing this new vision, issues remain for achieving more effective innovation diffusion and improved integrated care orientations. Discussion and evaluation: The case reveals that there was a failure to consider the health workforce in almost all of the reforms. Health and workforce policy became increasingly disconnected at the central and regional levels, leading to fragmentation, duplication and widening gaps. New Zealand’s more recent workforce policy and planning approach has adopted new tools and techniques to overcome these weaknesses that have implications for the workforce and service delivery, workforce governance and planning methodologies. However, further strengthening of workforce governance is required to embed the changes in policy and planning and to improve organisational capabilities to diffuse innovation and respond to evolving roles and team-based models of care. Conclusion: The case reveals that disconnecting the workforce from reform policy leads to a range of debilitating effects. By addressing how it approaches workforce planning and policy, New Zealand is now better placed to plan for a future of integrated and team-based health care. The case provides cues for other countries considering reform agendas, the most important being to include and consider the health workforce in health reform processes.